Validation of tractography: Comparison with manganese tracing. Issue 10 (14th July 2015) - Knösche, Thomas R.; Anwander, Alfred; Liptrot, Matthew; Dyrby, Tim B.
Abstract: In this study, we used invasive tracing to evaluate white matter tractography methods based on ex vivo diffusion‐weighted magnetic resonance imaging (dwMRI) data. A representative selection of tractography methods were compared to manganese tracing on a voxel‐wise basis, and a more qualitative assessment examined whether, and to what extent, certain fiber tracts and gray matter targets were reached. While the voxel‐wise agreement was very limited, qualitative assessment revealed that tractography is capable of finding the major fiber tracts, although there were some differences between the methods. However, false positive connections were very common and, in particular, we discovered that it is not possible to achieve high sensitivity (i.e., few false negatives) and high specificity (i.e., few false positives) at the same time. Closer inspection of the results led to the conclusion that these problems mainly originate from regions with complex fiber arrangements or high curvature and are not easily resolved by sophisticated local models alone. Instead, the crucial challenge in making tractography a truly useful and reliable tool in brain research and neurology lies in the acquisition of better data. In particular, the increase of spatial resolution, under preservation of the signal‐to‐noise‐ratio, is key. Hum Brain Mapp 36:4116–4134, 2015 . © 2015 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc.